Penerapan Teknologi Full Stack dalam Pengembangan Sistem Formulir Digital Rumah Sakit Menggunakan Metode Waterfall Development - Nugrahaningtyas, Tia Ifania; Siregar, Herbert (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The healthcare sector currently faces significant challenges in patient data management, where manual medical recording often leads to inefficiency, the risk of data loss, and slow information access by medical personnel. The main problem faced by many hospitals is the suboptimal integration between patient data collection and centralized database systems, which hinders continuous care delivery. Therefore, this study aims to design and develop an integrated digital form system in a hospital environment to facilitate accurate, fast, and secure medical data recording. The proposed solution is the application of full-stack technology using the CodeIgniter framework, PHP programming language, and DBeaver for database management. This research employs the Waterfall Development method, which aligns with collaborative team workflows. The development process is divided into iterative stages, starting from task assignments based on interface mockups from the Project Manager, dynamic data processing, to code collaboration via GitHub. Every system update goes through a Pull Request mechanism and is comprehensively tested by the Quality Assurance (PDI) team to ensure functionality and prevent errors. The achieved results indicate that the full-stack approach combined with the Waterfall method successfully produces a responsive digital form prototype, minimizes bugs through rigorous code reviews, and accelerates software adaptation. The contribution of this research is providing a scalable architectural model for health information systems, which can serve as a reference for medical institutions in executing digital transformation in healthcare services.